Efficiency of Ilmenite Photocatalyst Material as Modelling for Antimicrobial Activity - Nurdin, Muhammad; Yanti, Nur Arfa; Suciani; Watoni, Abdul Haris; Maulidiyah; Aladin, Andi; Wibowo, Dwiprayogo (Asian Journal of Chemistry, 2018)
Preparation of ilmenite (FeTiO3) composite for antimicrobial under UV-visible lights irradiation was carried out to appropriate as a new antimicrobial material. The preparation of FeTiO3 by using sol-gel method was conducted by the titanium tetra-isopropoxide (TTIP) as precursor titania and added Fe(NO3)3 as Fe source. Subsequently, the antimicrobial test (Escherichia coli, Staphylococcus aureus and Candida albicans) was carried out under photocatalysis system. The FeTiO3 was formed on 2θ of 20°, 24°, 36°, 48°, 53° and 62° having crystal size 53.75 nm. Scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) was investigated that the particle sized was under 100 nm and Fe element peak was on 6.398 keV. The antimicrobial test showedthat the efficiency of 15 % FeTiO3 was active under visible light irradiation to inhibit of E. coli, S. aureus and C. albicans with diameter zone were 18.778, 19.889 and 20.22 mm, respectively.